Quantitative Software Analysis of Ultrasonographic Textures in Experimental Testicular Torsion - Aslan, Mustafa; Kucukaslan, Ibrahim; Mulazimoglu, Serkan; Soyer, Tutku; Şenyücel, Mine; Çakmak, Murat; Scholbach, Jakob; Aslan, Selim (European Journal of Pediatric Surgery, 2013)
Aim Ultrasonography (US) has high diagnostic value in testicular torsion but is vulnerable to several potential errors, especially in the early period. Echotexture (ETX) analysis software provides a numerical expression of B-mode images and allows quantitative evaluation of blood flow due to ischemic damage using power Doppler US (PDUS) analysis. Our aim in this study was to determine the diagnostic value and effective parameters of EXT analysis software in the early period of torsion using B-mode and PDUS images.Materials and Methods In this study, eight rats were used. Following anesthesia, the right testis was rotated to a 1080-degree counterclockwise position whereas the left testis was left in place to have a control group. B-mode and PDUS images of both sides were recorded with a portable US device immediately (0 hour) and 1 and 2 hours after torsion. The B-mode images were analyzed in terms of gradient, homogeneity, and contrast using the BS200pro software (BAB Digital Imaging System 2007, Ankara, Turkey). Intensity (I)-red and area (A)-red values were measured on PDUS images with the Pixelflux (Version 1.0, Chameleon-Software, Leipzig, Germany). The data were evaluated by the Mann–Whitney U and Wilcoxon tests.Results Data from B-mode US image EXT analysis showed no significant difference between the right and left testicles in 0 to 2 hours (p > 0.05). The values obtained from PDUS analysis (I-red and A-red) significantly decreased at the testicular torsion side at the end of the second hour (p < 0.05). I-red and A-red values at 0 to 1 hour of torsion indicated similar blood flow alterations (p > 0.05) whereas the flow was significantly lower at 2 hours (p < 0.05).Conclusion In experimental testicular torsion, ischemic changes can be detected by PDUS power/angio mode using blood flow alterations as early as the second hour. Tissue damage cannot be evaluated within the first 2 hours of torsion with B-mode ETX analysis.
Keywords: testicular torsion; ultrasonography; echotexture; experiment; biomedical image processing